The Representation of Femininity in the Lyrics of Nizar Qabbani: A Connotative Semiotic Approach of Roland Barthes - Andi Khaeratul Ummah; Abdul Muntaqim Al Anshory; Nur Hasaniyah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2026)
The representation of women in modern Arabic poetry remains a significant scholarly focus, particularly in works that challenge traditional portrayals. Nizar Qabbani reconstructs feminine identity by depicting women as emotionally complex, intellectually dignified, and spiritually grounded. This study aims to reveal the connotative meanings in five poems from Asyhadu An Lā Imra’atan Illā Anti and explain how these signs construct a multidimensional image of women. Using a qualitative descriptive method supported by library research, the study applies Roland Barthes’ semiotics—especially second-order signification—to analyze symbolic signs, diction, and imagery. Primary data consist of Qabbani’s poems, while secondary data come from literature on semiotics and Arabic poetry. The findings show that Qabbani presents women as central emotional and existential forces: caregivers, spiritual guides, poetic inspirations, and individuals shaped by cultural pressures. His poetry dismantles stereotypes and reframes femininity through symbols of inner strength, resilience, and emotional honesty. Thus, women appear as active subjects shaping meaning, identity, and human experience